2021
DOI: 10.1021/acscatal.0c04325
|View full text |Cite
|
Sign up to set email alerts
|

The Stereochemical Course of Pd-Catalyzed Suzuki Reactions Using Primary Alkyltrifluoroborate Nucleophiles

Abstract: Using deuterium-labeled stereochemical probes, we show that primary alkyltrifluoroborate nucleophiles undergo transmetalation to palladium exclusively via a stereoretentive pathway and that the resulting stereospecificity is broadly independent of electronic and steric effects. This stands in stark contrast to the stereochemical course of transmetalation for secondary alkyltrifluoroborates, which varies between net stereoretention and net stereoinversion depending upon the electronic properties of the supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Because for this probe molecule the preference for anti-conformation is not as strong as that for molecule 1, the coupling constants for the threo-and erythro-isomers of product 4a have little difference. To identify these isomers clearly, a standard 1:1 diastereomeric mixture sample of 4a was synthesized under standard Catellani conditions (Scheme 4c), and the relationship between the magnitude of the H 1 − H 2 coupling constant and the relative configuration of compound 4a was assigned based on the previous investigation of Biscoe et al 19 Careful overlay of the 1 H{ 2 H} NMR spectra confirmed that threo-2 afforded eythro-4a and eythro-2 afforded threo-4a (Figure S12), indicating that complete inversion of configuration at the reaction center occurred at palladacycle complex 2. Thus, we can conclude that both Catellani-type palladacycles tend to undergo an S N 2 reaction with primary alkyl iodides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because for this probe molecule the preference for anti-conformation is not as strong as that for molecule 1, the coupling constants for the threo-and erythro-isomers of product 4a have little difference. To identify these isomers clearly, a standard 1:1 diastereomeric mixture sample of 4a was synthesized under standard Catellani conditions (Scheme 4c), and the relationship between the magnitude of the H 1 − H 2 coupling constant and the relative configuration of compound 4a was assigned based on the previous investigation of Biscoe et al 19 Careful overlay of the 1 H{ 2 H} NMR spectra confirmed that threo-2 afforded eythro-4a and eythro-2 afforded threo-4a (Figure S12), indicating that complete inversion of configuration at the reaction center occurred at palladacycle complex 2. Thus, we can conclude that both Catellani-type palladacycles tend to undergo an S N 2 reaction with primary alkyl iodides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because for this probe molecule the preference for anti-conformation is not as strong as that for molecule 1, the coupling constants for threoand erythro-isomers of product 4a have little difference. To identify these isomers clearly, a standard 1:1 diastereomeric mixture sample of 4a was synthesized under standard Catellani conditions (Scheme 4c), and the relationship between the magnitude of H 1 -H 2 coupling constant and the relative configuration of compound 4a was assigned based on the previous investigation of Biscoe et al 17 Careful overlay of the 1 H{ 2 H} NMR spectra confirmed that threo-2 afforded eythro-4a, and eythro-2 afforded threo-4a (Figure S12), indicating that complete inversion of configuration at the reaction center occurred at palladacycle complex 2. Thus, we can conclude that both Catellani-type palladacycles tend to undergo an S N 2 reaction with primary alkyl iodides.…”
Section: Suitable Reaction Conditionsmentioning
confidence: 99%
“…In a stereospecific cross-coupling reaction of chiral organoboron reagents, the stereochemical outcome is governed by the mechanism over the course of transmetalation, which usually follows an S E 2-type mechanism . A stereoretentive pathway is commonly observed, although several factors, including internal coordination by the substrate, supporting ligand, steric nature of nucleophile, or additives, are known to influence the process. To shed light on the robust stereoinvertive transmetalation of our system, we used density functional theory computations using Gaussian 16 with PBE-D3BJ/6-31G(d) and LANL2DZ.…”
mentioning
confidence: 99%